2012
DOI: 10.1021/la3038457
|View full text |Cite
|
Sign up to set email alerts
|

Controlled, Low-Coverage Metal Oxide Activation of Silicon for Organic Functionalization: Unraveling the Phosphonate Bond

Abstract: Deposition of thin films and grafting of organic molecules on semiconductor surfaces, particularly oxide surfaces, are widely studied as means of passivation and functionalization for a variety of applications. However, organic functionalization of silicon oxide is challenging, as the currently used molecules (silanes and phosphonates) do not form layers that are stable in aqueous environments and present challenges during the grafting process. For instance, the chemical grafting of phosphonates requires high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 81 publications
1
29
0
3
Order By: Relevance
“…Figure (bottom line) shows all of the typical spectral features of a monodentate phosphonic acid:11, 26–28 the stretch mode of the (P = O) at 1227 cm −1 , the asymmetric and symmetric stretch modes of the (P–O) at 1078 and 1004 cm −1 , and the deformation mode of the (P–O–H) feature clearly present at 956 cm −1 29. In the aliphatic region, the spectral positions of the strong asymmetric and symmetric stretch modes of the (CH 2 ) at 2918 and 2850 cm −1 , respectively, indicate an ordered arrangement on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Figure (bottom line) shows all of the typical spectral features of a monodentate phosphonic acid:11, 26–28 the stretch mode of the (P = O) at 1227 cm −1 , the asymmetric and symmetric stretch modes of the (P–O) at 1078 and 1004 cm −1 , and the deformation mode of the (P–O–H) feature clearly present at 956 cm −1 29. In the aliphatic region, the spectral positions of the strong asymmetric and symmetric stretch modes of the (CH 2 ) at 2918 and 2850 cm −1 , respectively, indicate an ordered arrangement on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The AlÀOÀH deformation mode is also present near 850 cm À1 . This mode was observed at 840 cm À1 for the condensation reaction of octadecylphosphonic acid onto aluminum oxide/hydroxide surface [26] and measured near 840-847 cm À1 in kaolinites [27]. However, the associated AlÀOÀH stretching modes are expected between 3200 and 3700 cm À1 [28] where they overlap with the HÀOÀH stretching mode of water.…”
Section: Materials Characterizationmentioning
confidence: 86%
“…1 The degree of aggregation can be controlled by playing with the pH or salt content in order to tune electrostatic repulsions. 15,16 Actually, very few studies have been reported on the surface modification of aqueous colloidal silica by organotrialkoxysilanes. 12,13 Functionalization of silica is usually done by grafting organotrialkoxysilanes, see, e.g., ref.…”
Section: Introductionmentioning
confidence: 99%